Developing an Interdisciplinary Environmental Educational Program on Insect Conservation for Primary School Children - Geanina M. Sitar; Cristian Sitar; Alina S. Rusu (Babes-Bolyai University, 2023)
Environmental education plays a critical role in shaping sustainable behaviours and cultivating a deeper understanding of ecological systems. This paper presents a theoretical framework supporting the interdisciplinary design of an environmental educational program in primary schools, with a specific focus on insect conservation. Insects, as vital contributors to ecosystem functioning, require dedicated attention and conservation efforts, making them an ideal focal point for engaging young learners. The proposed framework integrates essential components necessary for the elaboration of activities and learning objectives of the program, such as: effective environmental education, encompassing knowledge acquisition, attitude formation, and behavioural change. It emphasizes the provision of comprehensive and accurate information about insects, including their ecological roles and the challenges they face. To encourage behavioural change and a sense of responsibility, the framework underscores the need for hands-on experiences and direct interaction with insects. Practical activities, such as observing living insects can enable primary school students to develop a personal connection with insects and foster a sense of responsibility for their conservation. Furthermore, the framework underscores the importance of fostering positive attitudes towards insects, challenging any pre-existing negative perceptions, and nurturing empathy towards these invaluable species.